Molecular Transition Metal Oxide Electrocatalysts for the Reversible Carbon Dioxide–Carbon Monoxide Transformation. Issue 5 (20th December 2021) - Azaiza‐Dabbah, Dima; Vogt, Charlotte; Wang, Fei; Masip‐Sánchez, Albert; de Graaf, Coen; Poblet, Josep M.; Haviv, Eynat; Neumann, Ronny
Abstract: Carbon monoxide dehydrogenase (CODH) enzymes are active for the reversible CO oxidation–CO2 reduction reaction and are of interest in the context of CO2 abatement and carbon‐neutral solar fuels. Bioinspired by the active‐site composition of the CODHs, polyoxometalates triply substituted with first‐row transition metals were modularly synthesized. The polyanions, in short, SiM3 W9 and SiM′2 M′′W9 , M, M′, M′′=Cu II, Ni II, Fe III are shown to be electrocatalysts for reversible CO oxidation–CO2 reduction. A catalytic Tafel plot showed that SiCu3 W9 was the most reactive for CO2 reduction, and electrolysis reactions yielded significant amounts of CO with 98 % faradaic efficiency. In contrast, Fe–Ni compounds such as SiFeNi2 W9 preferably catalyzed the oxidation of CO to CO2 similar to what is observed for the [NiFe]‐CODH enzyme. Compositional control of the heterometal complexes, now and in the future, leads to control of reactivity and selectivity for CO2 electrocatalytic reduction. Abstract : A modular synthesis of trimetallo‐substituted polyanions enables the preparation of designer catalysts. Here this approach was used to prepare electrocatalysts for the selective reduction of CO2 to CO using a tri‐copper‐substituted polyanion. In contrast, Fe–Ni‐substituted polyanions preferably catalyzed the oxidation of CO to CO2, showing a reactivity profile reminiscent of the reactivity of Fe–Ni‐based carbon monoxide dehydrogenase enzymes.